Diagnostic value of magnetic resonance versus computed tomography colonography for colorectal cancer: A PRISMA-compliant systematic review and meta-analysis. Issue 22 (June 2018) - Sun, Shuangyan; Yang, Changliang; Huang, Zhicheng; Jiang, Wen; Liu, Yan; Wu, Hongfen; Zhao, Jihong
Abstract: Background: Advanced colorectal cancers were associated with poor prognosis, and early diagnosis was important for high-risk patients. Colonography is commonly used for diagnosing colorectal cancer. However, a few studies reported the diagnostic value of magnetic resonance colonography (MRC) versus computed tomography colonography (CTC). This study aimed to compare the diagnostic value of MRC versus CTC for colorectal cancer. Methods: Twenty-three studies on the diagnosis of colorectal cancer using MRC or CTC were obtained from PubMed, Embase, and the Cochrane Library databases until July 2017. The ratios of sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and receiver operating characteristic (ROC) curve were calculated to compare the diagnostic value of MRC versus CTC. Results: The summary sensitivity, specificity, PLR, NLR, and area under the ROC for MRC were 0.97 (0.81–1.00), 0.92 (0.80–0.97), 11.71 (4.46–30.73), 0.03 (0.00–0.24), and 0.98 (0.97–0.99), respectively, for diagnosing colorectal cancer. The pooled estimates for CTC in diagnosing colorectal cancer were as follows: sensitivity, 0.96 (0.90–0.98); specificity, 1.00 (0.99–1.00); PLR, 197.32 (73.21–531.85); NLR, 0.04 (0.02–0.11); and area under the ROC, 1.00 (0.99–1.00). No significant differences were found between MRC and CTC for sensitivity, specificity, and NLR. MRC was associated with lower PLR and area under the ROC for diagnosing colorectal cancer compared with CTC. Conclusion: This study demonstrated MRC and CTC as potential diagnostic approaches for colorectal cancer. CTC had a higher diagnostic value of PLR and area under the ROC for colorectal cancer.